2018
DOI: 10.1051/matecconf/201815005060
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Talent Management in the Relationships between Employee Engagement: A Study of GLCs

Abstract: Talent management practice is crucial in relating the potential talent. The GLCs need to have a potential talent in order to continue the value creation for business competitiveness. Moreover, talent that possesses high level of commitment and engagement will add value in the organization. This study aims to examine the relationship between talent management practices and employee engagement of employees at GLCs. The sample included 230 employees, which were selected randomly. For this study the method for dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
(22 reference statements)
1
9
0
Order By: Relevance
“…The results showed that employee engagement was able to improve talent management optimization by 34.1%. This study supports several studies that show the positive effect of employee engagement on talent management (Aizat Ramli et al, 2018;O'Connor & Crowley-Henry, 2019;Sopiah et al, 2020). Employee engagement runs optimally by increasing participation in the company's business processes.…”
Section: Employee Engagement On Talent Managementsupporting
confidence: 89%
See 1 more Smart Citation
“…The results showed that employee engagement was able to improve talent management optimization by 34.1%. This study supports several studies that show the positive effect of employee engagement on talent management (Aizat Ramli et al, 2018;O'Connor & Crowley-Henry, 2019;Sopiah et al, 2020). Employee engagement runs optimally by increasing participation in the company's business processes.…”
Section: Employee Engagement On Talent Managementsupporting
confidence: 89%
“…Employee engagement is an idea in organizational behavior that has become an attraction for organizational leaders or in recent years. Several studies have shown that employee engagement affects talent management (Aizat Ramli et al, 2018;O'Connor & Crowley-Henry, 2019;Sopiah et al, 2020). This attraction arises because employee engagement has an indirect effect on the overall performance of the company.…”
Section: Literature Review Employee Engagement On Talent Managementmentioning
confidence: 99%
“…The results in Figure 1 above showed that 47.0 and 32% of the respondents rated poor and very poor, respectively, implying that application of talent management practices were rated poorly by registered nurses in public hospitals in all four constructs. Hence, the study hypothesis was accepted because studies demonstrate that talent management practices are largely not well applied in organisations (Barkhuizen et al, 2014a;Ramli et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrate that the manner in which employees perceive the way talent management practices are applied in their respective organisations would determine their intention to stay or leave the organisation and this holds true for the nurses in public hospitals (Mousa and Ayoubi, 2019;Ramli et al, 2018). Furthermore, in the healthcare contexts, studies have undeniably demonstrated that there is a growing realisation of the poorly developed scope and shortage of empirical studies on the topic of talent management (King, 2015;Mousa and Puhakka, 2019).…”
Section: Ajems 123mentioning
confidence: 99%
“…Similarly, talent management practices can serve as important instruments to facilitate the achievement of employee outcomes such as retention, commitment, organisational citizenship behaviour, performance, motivation, job satisfaction, and work engagement (Ashe 2018;Burbach, Scroggins, and Royle 2010;Chien and Yick 2016;Ramli et al 2018). Many studies have also demonstrated that talent management promotes innovative work behaviour of employees (Asurakkody and Young 2018;Bawuro et al 2018;Khaki et al 2017;Shu-pei 2018).…”
Section: Talent Management Practicesmentioning
confidence: 99%